2012
DOI: 10.1183/09031936.00029412
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to an early switch from intravenous to oral antibiotic therapy in hospitalised patients with CAP

Abstract: Do physicians apply an early-switch strategy (from intravenous to oral antibiotics) in clinically stable patients hospitalised with community-acquired pneumonia (CAP)? If not, why not?In a multicentre prospective cohort study, adult patients admitted for i.v. CAP treatment were included. On day 3 of antibiotic treatment, clinical stability was assessed and treating resident physicians were interviewed on their switch strategies. Additionally, treating physicians were interviewed to evaluate their knowledge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 23 publications
4
38
0
1
Order By: Relevance
“…Potentially, ES and ED programmes may benefit by administration of IV antibiotics with highly bioavailable oral formulations, by offering precise guidelines regarding which oral antibiotics can be substituted for IV antibiotics or be used to treat specific conditions, or by providing an infectious disease consult [46]. Other prescriber-specific barriers identified include time constraints, rapid rotation of physicians in charge of patients, and the belief that IV therapy is superior to oral therapy [22,44]. …”
Section: Prescriber Levelmentioning
confidence: 98%
See 1 more Smart Citation
“…Potentially, ES and ED programmes may benefit by administration of IV antibiotics with highly bioavailable oral formulations, by offering precise guidelines regarding which oral antibiotics can be substituted for IV antibiotics or be used to treat specific conditions, or by providing an infectious disease consult [46]. Other prescriber-specific barriers identified include time constraints, rapid rotation of physicians in charge of patients, and the belief that IV therapy is superior to oral therapy [22,44]. …”
Section: Prescriber Levelmentioning
confidence: 98%
“…Unit/hospital level Barriers to ES and ED at a unit/hospital level include staffing time constraints, staffing changes and prescribing etiquette [43,44]. Reassessment of antimicrobial therapy after 48-72 h of treatment is often neglected because of time constraints and changes in staffing [19].…”
Section: Barriers To Implementationmentioning
confidence: 99%
“…However, the literature shows that this is not common practice 4. In this study, the authors identified that 94% of physicians who treated these patients were unaware of available guidelines for the timing of the switch from  intravenous to oral antibiotics.…”
Section: Commentarymentioning
confidence: 96%
“…Patient factors (eg, comorbidities) or physician factors (eg, reluctance to stop β-lactam treatment or not being aware of guideline advice) may impede a switch to TT in case of a positive LUAT result 9. To date, it is unknown to what extent current use of the LUAT leads to timely detection of Legionella spp.…”
Section: Introductionmentioning
confidence: 99%